2021
DOI: 10.3390/plants10020419
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Control of Plant Functions: Ecological and Agricultural Implications

Abstract: Potassium, mostly as a cation (K+), together with calcium (Ca2+) are the most abundant inorganic chemicals in plant cellular media, but they are rarely discussed. K+ is not a component of molecular or macromolecular plant structures, thus it is more difficult to link it to concrete metabolic pathways than nitrogen or phosphorus. Over the last two decades, many studies have reported on the role of K+ in several physiological functions, including controlling cellular growth and wood formation, xylem–phloem water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 307 publications
3
69
1
6
Order By: Relevance
“…Better performance of sunflower in terms of yield and yield components under higher K fertilization is due to the involvement of K in main osmotic solute of plants [ 28 , 37 ]. Potassium accumulation at the cellular level results in osmotic water uptake and generation of cell turgor needed for stomatal opening and plant growth [ 38 , 39 ]. Potassium influx inside the stomatal guard cells cause water accumulation leading to their swelling and subsequent stomatal opening, allowing CO 2 and transpired water vapors to move freely in and out of plant tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better performance of sunflower in terms of yield and yield components under higher K fertilization is due to the involvement of K in main osmotic solute of plants [ 28 , 37 ]. Potassium accumulation at the cellular level results in osmotic water uptake and generation of cell turgor needed for stomatal opening and plant growth [ 38 , 39 ]. Potassium influx inside the stomatal guard cells cause water accumulation leading to their swelling and subsequent stomatal opening, allowing CO 2 and transpired water vapors to move freely in and out of plant tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In case of inadequate supply of K, the stomatal activity becomes slow and water losses are high. However, adequate K supply increases plant uptake of water as well as improves its use efficiency within the plant [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Litter quality, which is mainly determined by the relative content of recalcitrant organic compounds (e.g., lignin or phenols) and macronutrients, is of particular importance in controlling the mass loss and dynamics of litter nutrients during decay under similar climatic conditions (Prescott et al, 2000;Berg and McClaugherty, 2008). Several studies have shown that high initial nitrogen (N), phosphorus (P), and potassium (K) concentrations in litter regulate the early stages of decomposition by stimulating the decay of celluloses and solubles (Berg and Staaf, 1980;Berg and Matzner, 1997;Chen et al, 2002;Cusack et al, 2009;Sardans and Penuelas, 2021). However, high N inhibits the decay in the later stages by suppressing the activity of lignolytic enzymes (Carreiro et al, 2000) and shifting the decomposercommunity composition (Couteaux et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…K is taken up very efficiently and longdistance transport occurs in the xylem and phloem throughout the plant. K is involved in all aspects of plant growth and has many different functions [1]. By adjusting plant water requirements through influencing the transpiration process [2], K plays a key role in the transport of photosynthates, the regulation of stomatal physiological mechanisms, the synthesis of carbohydrates [3], and is directly related to the regulation of the cell osmotic potential to minimize stress responses [4].…”
Section: Introductionmentioning
confidence: 99%